Optimizing Agricultural Yields with Artificial Intelligence-Based Climate Adaptation Strategies - Zidan, Fallen; Febriyanti, Dita Evia (IAIC Transactions on Sustainable Digital Innovation (ITSDI), 2024)
In the face of climate change, agricultural productivity is severely threatened by unpredictable weather patterns and changing environmental conditions, underscoring the critical need for innovative solutions to bolster agricultural resilience and optimize yields. This study delves into the potential of artificial intelligence (AI), specifically through the use of machine learning and deep learning techniques, to develop climate adaptation strategies aimed at enhancing agricultural outcomes. By integrating AI with climatological data, the research predicts and mitigates the adverse impacts of climate on crop yields, utilizing a combination of machine learning and deep learning models to analyze historical climate data alongside crop performance. These models, trained on datasets including temperature, rainfall, soil moisture, and crop genetic information, are adept at forecasting future agricultural outcomes under varied climatic scenarios and suggest optimal adaptation strategies that significantly improve crop yields. Consequently, these AI-based models serve as robust tools for farmers and agricultural policymakers, enabling them to make informed decisions that are aligned with anticipated climatic conditions. The findings not only underscore the efficacy of AI in transforming data into actionable insights that enhance agricultural productivity but also contribute to the field of agricultural science by providing a technologically advanced approach to climate adaptation. Furthermore, this research paves the way for future studies on the integration of AI with real-time environmental sensing technologies, thereby offering a dynamic framework for agricultural management that supports sustainable farming practices and global food security amid climate challenges.